Agro-climatic risk and irrigation need of the Nilwala Basin, southern Sri Lanka - Weerasinghe, K. D. N., author; Elkaduwa, W. K. B., author; Panabokke, C. R., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Climate potential in respect to onset, magnitude and risk associated with rainfall for crop production in the Nilwala basin, Southern Sri Lanka was assessed using the daily rainfall of 12 stations scattered in different locations for more than 35 consecutive years (1950-1995). The program CROPWAT was used to assess the irrigation need. It was revealed that rainfall of the basin increases from south to north with increasing elevation and altitude. Within a 70-km distance in the south north gradient, rainfall elevates from 1656 mm at Kekanadura to 4216 mm at Kudawa. The net irrigation requirement of Yala rice in different locations varied from 1012 mm to 1246 mm. It was established that the irrigation need in the Nilwala upper catchment is below 40 % of the total water requirement, but in downstream areas it constitutes above 70% of the total water demand. Therefore both the Yala and Maha seasons in Nilwala downstream areas appeared to be unsuitable for rice cultivation without supplementary irrigation. From April 10th onward until May 20th is the best period for establishment of perennial crops at upper catchment areas. Optimum dates for crop establishment at the mid and lower part of the catchment falls on the 14th meteorological week. It is important to note that delaying crop establishment in Yala by 2 or 3 weeks from the optimum date would result in a considerable increase of irrigation need even in the upper catchment areas; it is not advisable to delay the establishment of Maha rice until October when rice varieties off our month duration are cultivated.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.